LAMPS OF TUNKAT FROM THE 9TH–12TH CENTURIES (TYPOLOGY AND ARTISTIC DECORATION FEATURES) - Boburmirzo Jo‘raqulov (Western European Studies, 2025)
This article analyzes the form, technique, and artistic features of lamps discovered at the archaeological site of the city of Tunkat (9th–12th centuries). During the study, several types of glazed and unglazed lamps in white, brown, and silver hues were examined, and their typological classification was carried out. Each specimen is described in terms of technical measurements, decorative patterns, manufacturing techniques, and intended use. The analysis revealed a harmonious synthesis of Islamic artistic aesthetics, Kufic inscriptions, and local stylistic traditions in the production of these lamps. The lamps of Tunkat represent an important archaeological source for illuminating the material culture of medieval Central Asia
Keywords: Tunkat; lamp; glazed ceramics; Kufic script